Mediastinal metastasis of primary extraneural ependymoma: A case report - Andrejic Višnjić, Bojana M; Tegeltija, Dragana; Lovrenski, Aleksandra; Vučković, Dejan; Samardžija, Golub; Tadić Latinović, Ljiljana (Vojnosanitetski pregled, 2020)
Introduction. The rarity of primary extraneural ependymomas (EnEs), its great variations in morphology and rare occurrence of metastasis, increase chances of misdiagnosis, particularly if they are found in paraovarian localization. Case report. The presented patient was diagnosed with malignant mesothelioma 14 years ago, after right salpingo-oophorectomy. In following years patient had multiple and extensive surgical procedures, resulting in different histopathological diagnoses, and after seven years, a diagnosis of EnE was established. Later on, patient was surgically treated in several medical centers across the region, again with different histopathological diagnoses. At present, the tumor metastasized to mediastinum, presenting as a grey to brown, multicystic formation with cysts filled with a clear serous fluid or red-brown hemorrhagic fluid. The inner surface of the cysts had smooth to partly papillary appearance. Tumor cells exhibited several architectural patterns (solid, pseudorosette or rosette formations, papillary and pseudopapilary structures), and immunophenotype specific for EnE [glial fibrillary acidic protein (GFAP), estrogen receptor (ER), and progesterone receptor (PR) positive; calretinin, WT-1, S100, synaptophysin, chromogranin, CK7 and pan-cytokeratin negative]. Conclusion. This case demonstrates not only specific diagnostic immunophenotype of extraneural ependymoma, but above all an important principle in tumor pathology. Rare neoplasms may occur in unusual and unexpected primary and metastatic sites. Pathologists need to be familiar with histologic features of a wide range of neoplasms and not just the appearance of neoplasms within their own limited subspecialty area.